Współzawodnictwo pracy w działalności Komitetu Wojewódzkiego Polskiej Partii Robotniczej (KW PPR) w Kielcach (1945-1948) - Trepka, Tomasz (Komunizm: System - Ludzie - Dokumentacja, 2014)
Polish Workers' Party (PPR) were particular about work competition. It was to be an element of political operations (to create a new working class and to perform educational function) and economic (to increase and improve the quality of production). However, The Communist Party encountered a number of difficulties in production plants. The most important of these may include the independence of the parts of the administration of companies and trade unions, insufficient involvement of some members of the Communist Party and the reluctance on the workers. Despite those facts, work competition was forcing in the most of companies in Kielce province and was an integral part of socio - economic development in post-war Poland.